Stuck in a Moral Prison: Exploring the Roots of Why Indonesian Students Moralize Literature - Donelson-Sims, Danielle E. (k@ta: A Biannual Publication on the Study of Language and Literature, 2013)
This paper explores a belief in Indonesian culture, held by educators and students, that literature teaches morals. While learning literature offers a potential benefit, a problem arises when instilling and/or recycling moral knowledge is recognized as the only reason to learn literature. When identifying established morals becomes the stopping point, other elements may be ignored, such as critical thinking, culture, history, perspectives, and marginalization. Four literature lecturers and seven students were interviewed. Data revealed all participants had varying definitions of “morals,” leading to potential classroom confusion. All participants agreed morals ought to be considered, but only the (majority of) students identified them as the most important in literary study. Additionally, not all students enjoyed finding morals; some were rather bored by examining morals. Lastly, most participants believed Indonesian culture and education contributes to the habit of searching for morals, and valuing them at the expense of other learning benefits.